If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -13 = -47 Reorder the terms: -13 + x = -47 Solving -13 + x = -47 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '13' to each side of the equation. -13 + 13 + x = -47 + 13 Combine like terms: -13 + 13 = 0 0 + x = -47 + 13 x = -47 + 13 Combine like terms: -47 + 13 = -34 x = -34 Simplifying x = -34
| -0.7x^2+42x=0 | | 5(7n+32)+8(n+1)n=425 | | (3/7)m+(1/2)=10 | | 4-13=-47 | | 3(y+7)-5y=17 | | 15=8x-25 | | 5x+1=1x+49 | | 8+q+5=3 | | 5(7n+32)+8(n+1)= | | -11v-8+3v=24 | | q-3+6=1 | | 1/4x+5=10 | | 3(4)+4y=84 | | -3(4y-5)+2(3y+9)= | | -8=16 | | x-18+=3X | | 0.333h-4(0.667h-3)=0.667h-6 | | 3x+4(0)=84 | | -6z+6z=6 | | 7+4x=6x+25 | | 2x^2-12x-18=0 | | 3(0)+4y=84 | | 9x-4+x=24+10x | | X^2-52=-3 | | -(0)-4y=6 | | 16-22=-2x | | 6xn-9=-15 | | 1024+4x=12 | | 4(x-1)-(2-x)=5(x-2)+4 | | -x-4(0)=6 | | -x+2=3x+4x | | -15=3x+6 |